2013
DOI: 10.1038/aps.2012.199
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells transplantation suppresses inflammatory responses in global cerebral ischemia: contribution of TNF-α-induced protein 6

Abstract: Aim: To investigate the effects of mesenchymal stem cells (MSCs) transplantation on rat global cerebral ischemia and the underlying mechanisms. Methods: Adult male SD rats underwent asphxial cardiac arrest to induce global cerebral ischemia, then received intravenous injection of 5×10 6 cultured MSCs of SD rats at 2 h after resuscitation. In another group of cardiac arrest rats, tumor necrosis factor-α-induced protein 6 (TSG-6, 6 µg) was injected into the right lateral ventricle. Functional outcome was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…TSG-6 expression in keloid scars is lower than in normal scars but higher than in normal skin; the expression and distribution of HA and IαI are consistent with those of TSG-6 (Lin et al, 2013). HA reduces scar formation by inhibiting fibroblast differentiation and decreasing inflammation, primarily by inhibiting prostaglandin E2 levels, inflammatory cell chemotaxis and oxygen free radical production (Mast et al, 1992;Schimizzi et al, 2006).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…TSG-6 expression in keloid scars is lower than in normal scars but higher than in normal skin; the expression and distribution of HA and IαI are consistent with those of TSG-6 (Lin et al, 2013). HA reduces scar formation by inhibiting fibroblast differentiation and decreasing inflammation, primarily by inhibiting prostaglandin E2 levels, inflammatory cell chemotaxis and oxygen free radical production (Mast et al, 1992;Schimizzi et al, 2006).…”
Section: Discussionmentioning
confidence: 56%
“…TSG-6 contains a hyaluronan-binding link domain and can form a stable covalent complex with inter-alpha-inhibitor (IαI), which is important in the protease network associated with inflammation. This antiinflammatory effect of TSG-6 has been confirmed in many studies (Getting et al, 2002;Lin et al, 2013;Nagyeri et al, 2011). In 2010, Tan showed that the anti-inflammatory factor TSG-6 was differentially distributed in keloid scars, normal scars and unscarred skin (Tan et al, 2011).…”
Section: Introductionmentioning
confidence: 65%
“…Stereotaxic coordinates were 0.8 mm (anteroposterior), 1.5 mm (lateral), and 4.0 mm (depth) [23]. The localization of the cannula was tested by evaluating the dipsogenic response to an intracerebroventricular (icv) angiotensin II injection (5 ng/μL saline; Sigma, St. Louis, MO, USA) 1 week after the surgical procedure (7th week of fructose treatment).…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences were as follows: for C3, forward 5-CTGTACGGCATAGGGATATCACG-3, reverse 5-ATGCTGGCCTGACCTTCAAGA-3 (Misumi et al, 1990); for C1q, forward 5-ACCCAGACTTCCGCTTTCTG-3, reverse 5-CTTCAGGGGCCTCCTGTGTA-3 (selfconstricted); for β actin, forward 5-GCGCTCGTCGTCGACAACGG-3, reverse 5-GTGTGGTGCCAAATCTTCTCC-3 (Kit provided); for GAPDH, forward 5-CAAGGTCATCCATGACAACTTTG-3, reverse, 5-GTCCACCACCCTGTTGCTGTAG-3 (Lin et al, 2013); for C3a forward 5-GACCTACACTCAGGGC-3, reverse 5-ATGACG GACGGGATAAG-3 (Benard et al, 2004); for forward SYP 5-TCAGGACTCAACACCTCAGTGG-3 reverse 5-AACACGAACCATAAGTTGCCAA-3 (Chen et al, 2001).…”
Section: Western Blot Analysis and Qrtpcrmentioning
confidence: 99%